Perbedaan Perilaku Asertif Anak Sulung Berdasarkan Gender serta Implikasinya terhadap Layanan Bimbingan dan Konseling - Rahayu, Siti Sri; Netrawati, Netrawati; Sari, Azmatul Khairiah; Febriani, Rahmi Dwi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study aims to examine gender differences in assertive behavior among firstborn students and to analyze the implications for school guidance and counseling services. The research employs a quantitative descriptive comparative approach with 60 respondents (30 male and 30 female firstborn students) selected using purposive sampling. Data were collected using a validated assertiveness scale covering seven aspects: expressing feelings, rejecting requests, initiating interactions, expressing personal opinions, defending personal rights, requesting changes in others, and facing criticism. Statistical analysis revealed that male firstborn students demonstrate higher levels of assertiveness than their female counterparts across most indicators. These findings suggest that gender plays a significant role in shaping assertive behavior among firstborns, likely influenced by sociocultural expectations and familial roles. The results underscore the importance of implementing gender-responsive guidance and counseling strategies in schools to foster healthy communication, self-confidence, and emotional resilience among students, particularly those experiencing role pressure as firstborns.